Paclitaxel, Imatinib and 5-Fluorouracil Increase the Unbound Fraction of Flucloxacillin In Vitro - Maximilian Stolte; Weaam Ali; Janne Jänis; Andre' Gessner; Nahed El-Najjar (MDPI AG, 2020)
Flucloxacillin (FLU), an isoxazolyl penicillin, is widely used for the treatment of different bacterial infections in intensive care units (ICU). Being highly bound to plasma proteins, FLU is prone to drug-drug interactions (DDI) when administered concurrently with other drugs. As FLU is binding to both Sudlow's site I and site II of human serum albumin (HSA), competitive and allosteric interactions with other drugs, highly bound to the same sites, seem conceivable. Knowledge about interaction(s) of FLU with the widely used anticancer agents paclitaxel (PAC), imatinib (IMA), and 5-fluorouracil (5-FU is scarce. The effects of the selected anticancer agents on the unbound fraction of FLU were evaluated in pooled plasma as well as in HSA and α-1-acid glycoprotein (AGP) samples, the second major drug carrier in plasma. FLU levels in spiked samples were analyzed by LC-MS/MS after ultrafiltration. Significant increase in FLU unbound fraction was observed when in combination with PAC and IMA and to a lesser extent with 5-FU. Furthermore, significant binding of FLU to AGP was observed. Collectively, this is the first study showing the binding of FLU to AGP as well as demonstrating a significant DDI between PAC/IMA/5-FU and FLU.